Peers as Facilitators of Medication Adherence Interventions - Maithe Enriquez; Vicki S. Conn (SAGE Publishing, 2016)
Background: Difficulty taking essential medications as prescribed is a prevalent problem among people living with chronic diseases. Numerous interventions to enhance medication adherence have been developed; the majority facilitated by health care professionals. Objective: This review examined medication adherence interventions delivered by peers (ie, lay individuals living with the same chronic disease) and reports what is known about the impact of peer-facilitated interventions. Data Sources: PubMed, CINAHL, Google Scholar, Google, and PsychInfo, and ancestry searches. Study Selection: Solely peers delivered the intervention and follow-up occurred for at least 24 weeks postintervention. Electronic databases were searched from their start date to December 31, 2014. Results: Eleven studies were located that reported 10 different interventions focused on 6 chronic disease conditions. Most interventions were delivered in clinical settings and grounded in a theoretical framework. Formats were evenly split between individual and group level, with one intervention using both. Length of training for the interventionists and the number of intervention sessions that subjects received varied across studies. Limitations: Self-report was frequently used as a measure of adherence. Biomarkers were sometimes used to assess medication adherence; however, lifestyle modification may have also affected biomarker levels. Conclusions: Overall, the interventions had positive effects and attrition was quite low. Peer-facilitated interventions appear to enhance medication adherence as well as other healthful behaviors, such as exercise.